Development of GeoGebra-Based PjBL Activities Containing Ethnomathematics in Spatial Geometry to Improve Mathematical Communication - Fajrul Falah; Mohamad Waluyo (Proceeding International Conference on Mathematics and Learning Research, 2025)
The low mathematical communication skills of junior high school students, particularly in presenting mathematical ideas and arguments in writing, form the background of this study. As a solution, a Project-Based Learning (PjBL) activity that integrates ethnomathematics content and is assisted by GeoGebra software was developed. This research is a development study (R&D) that adopted the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The aim of this research is to develop ethnomathematics-based Project-Based Learning activities and teaching tools assisted by GeoGebra on the topic of three-dimensional flat-sided shapes (cubes, cuboids, prisms, and pyramids), as well as to test their validity. The ethnomathematics context used is the architecture of the Dieng Temple to study the concept of surface area. The resulting product was assessed by subject matter and media experts. The validation results show an average score of 0.8542, which falls into the highly valid category. Therefore, the developed learning product is declared valid and feasible for use to support mathematical communication.